The Influence of Macroeconomic Variables on Problematic Financing in the Sector of Manufacturing - Rosye Rosaria Zaena; Enny Diah Astuti; Jefriyanto; Ifadhila; Sukma Irdiana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study intends to examine how Indonesia's problematic manufacturing industry sector funding in Islamic banking is affected by macroeconomic factors such exchange rates, inflation, BI rates, and export growth. Monthly time series data from January 2018 to December 2022 were used in this investigation. The multiple linear regression test is the statistical analysis employed in this investigation. The findings demonstrated that the troublesome financing of the Manufacturing Industry sector was significantly influenced by a combination of macroeconomic factors, including exchange rate, inflation, BI rate, and export growth. Partly, the difficult financing of the Manufacturing Industry sector is significantly impacted by both inflation and the BI Rate in both positive and negative ways.